Predominant bacteria and patterns of antibiotic susceptibility in urinary tract infection in children with spina bifida. Issue 5 (October 2018) - Ortiz, Tara K.; Velazquez, Nermarie; Ding, Laura; Routh, Jonathan C.; Wiener, John S.; Seed, Patrick C.; Ross, Sherry S.
Summary: Background: Urinary tract infection is more common in children with spina bifida (SB) than neurologically intact children, and Escherichia coli is the most common urinary pathogen in the general pediatric population. Less is known of the pathogens responsible for urinary tract infections (UTI) in the pediatric SB population or their evolving antimicrobial resistance patterns. The goal of this study is to determine the epidemiology and antimicrobial resistance patterns of SB-associated urinary pathogens. Methods: Between January 1996 and August 2013, 231 patients aged 1 month to 18 years were identified with a diagnosis of SB-NB and at least one symptomatic urinary tract infection (UTI) event (Table ). Two-hundred and thirty-one normally voiding children with a single symptomatic UTI were age-matched based on age at diagnosis of UTI at a 1:1 ratio. Chi-square tests and Generalized Estimating Equation analysis, controlling for clinicopathological factors, were performed to compare rates of pathogen-associations with UTI between groups and likelihood of UTI with multi-drug resistant (MDR) organisms. Results: Children in the SB-NB group had a higher rate of non- E. coli UTI compared with controls (64% vs. 41%, p < 0.01), particularly associated with Klebsiella species the SB-NB group had an overall higher infection rate with MDR organisms (21% vs. 10%, p < 0.01) and E. coli isolates, with a trend towards increased rates of antibiotic resistance to aminoglycosides, fluoroquinolones, cephalosporins, extended spectrum β-lactams, and TMP-SMZ. Additionally, patients in the SB-NB group had a 10-fold increase of urosepsis with 57% of events caused by MDR organisms. Conclusions: Children with SB-NB are more likely to have non- E. coli UTI, UTIs with MDR organisms, and urosepsis than the general pediatric population. Table Demographics of study population and risk factors associated with E. coli UTI and multi-drug resistant UTI. Spina bifida with neurogenic bladder Healthy children p-value Gender N = 231 (%) N = 231 (%) Male 85 37% 64 28% Female 146 63% 167 72% 0.02 Age at UTI N = 965 (%) N = 231 (%) Birth–47 months 306 32% 49 21% 48–155 months 447 46% 101 44% 156–227 months 212 22% 81 35% Race N = 231 (%) N = 231 (%) White 147 64% 109 47% <0.01 Black 35 15% 60 26% <0.01 Hispanic 30 13% 30 13% 0.92 Asian 4 2% 5 2% 0.77 Native American 1 0% 2 1% 0.40 Other 14 6% 25 11% 0.05 Circumcision N = 85 (%) N = 64 (%) Yes 52 61% 14 22% No 26 31% 18 28% Unknown 7 8% 32 50% Clean intermittent catheterization N = 231 (%) N = 231 (%) Yes 155 67% N/A Comorbidities:# of children w/diagnosis N = 231 (%) N = 231 (%) Hydronephrosis 100 43% 14 6% <0.01 Vesicoureteral reflux 63 27% 19 8% <0.01 Hypertension 28 12% 7 3% <0.01 Chronic kidney disease 23 10% 4 2% <0.01 Sepsis 7 3% 1 0.4% <0.01 Stones 18 8% 5 2% <0.01 Bladder reconstruction 44 19% N/A Bladder augment 26 59% N/A Catheterizable channel 18 41% N/A OR 95% CI p -value E. coli UTI Spina bifida and neurogenic bladder 0.42 0.30–0.58 <0.001 Age at diagnosis of UTI 1.01 0.98–1.03 0.52 Total number of UTIs 0.99 0.96–1.02 0.63 Female gender 3.16 2.31–4.32 <0.001 Multi-drug resistant UTI Spina bifida and neurogenic bladder 1.6 1.05–2.59 0.03 Age at diagnosis of UTI 0.97 0.92–1.01 0.17 Total number of UTIs 1.02 0.99–1.04 0.07 Prophylactic antibiotics 1.48 0.94–2.32 0.09